Respon Pertumbuhan dan Hasil Empat Kultivar Jagung Hibrida (Zea mays L.) dengan perlakuan pemupukan Nitrogen dalam sistem Agroforestri Kayu Putih (Melaleuca cajuputi Powell) - Sara Juanita Christanty; Taufan Alam; Dody Kastono (Vegetalika, 2025)
Maize (Zea mays L.) is one of the primary food crops and is widely utilized across various sectors. Cultivating maize under cajuput (Melaleuca cajuputi) stands often faces nutrient deficiency problems, primarily due to clay-textured soils with alkaline pH, which can limit the availability of both macro- and micronutrients, especially nitrogen. Nitrogen deficiency in maize significantly reduces its productivity. This study aimed to examine the growth and yield responses of four hybrid maize cultivars to nitrogen fertilization and to determine the optimum nitrogen dosage within an agroforestry system. The research was conducted from October 2024 to February 2025 in Srikoyo Hamlet, Bleberan Village, Playen Subdistrict, Gunung Kidul District, Yogyakarta Special Region Province, Indonesia. The experiment was arranged using a factorial randomized complete block design (RCBD) with three replications. The first factor consisted of four hybrid maize varieties: ADV Jago, NK 212, Pioneer 89, and R7 Gold. The second factor was urea fertilizer dosage: 0, 150, 300, and 450 kg/ha. Results showed that the productivity response of ADV Jago followed a quadratic pattern, while NK 212, R7 Gold, and Pioneer 89 exhibited a linear response. The optimum nitrogen dose for ADV Jago was 356.67 kg/ha, yielding a maximum productivity of 6.03 tons/ha, which represents an 83.28% increase compared to the unfertilized control. Meanwhile, application of 450 kg/ha nitrogen to NK 212, R7 Gold, and Pioneer 89 resulted in respective productivities of 6.65; 6.22; and 6.83 tons/ha, reflecting increases of 45.51%; 159.2%; and 123.93% compared to no nitrogen application, respectively.